Segmentation by motivation of tourists to the Kgalagadi Transfrontier Park - M. Saayman; T. Dieske (South African Journal of Business Management, 2015)
The Kgalagadi Transfrontier Park is one of South Africa's unique attractions for national and international tourists. However, little research has been done on visitors to transfrontier parks. In addition marketers highlight the importance of understanding the reasons why people travel and who these tourists are. Therefore the aim of this article is to segment the market of the Kgalagadi Transfrontier Park by means of visitors' travel motives. This was achieved by means of a survey. In the statistical analysis, 414 questionnaires were used and the survey was conducted from 2010 to 2012. The statistical analysis included a factor analysis and ANOVA. Four factors were identified through the factor analysis namely escape, education and recreation, park attributes and exploration. The latter was unique to this research since it has not been found in other studies. The ANOVA confirmed that a wide variety of variables influence the decision-making process and that the marketing strategy should focus on different methods and events to attract a greater market.
Keywords: 650